A critical assessment of the conciliation hearing in Germany and South Africa from a comparative point of view - Ilies, Ines (Department of Commercial Law, 2023)
This work gives an overview of the resolution of individual labour disputes through conciliation in Germany and South Africa. In a rapidly evolving labour environment, parties have an increased interest in obtaining legal clarity on the outcome of a dispute. Neither employers nor employees can afford delays. Access to justice is essential. An amicable settlement serves this aim and is likely to bring the dispute to a swift end in a speedy and inexpensive proceeding. Thus Germany and South Africa both developed a mechanism of mandatory conciliation as the starting point of every individual rights dispute, which aims to grant easy and fast access to justice at a low cost. In South Africa the Commission for Conciliation, Mediation and Arbitration (CCMA) has been established to resolve individual labour disputes through conciliation. In Germany a preliminary conciliation hearing takes place before the chairperson in the Labour Court of first instance. This work aims to critically assess the conciliation procedure in both countries, illustrate similarities and differences and suggest improvements. The question that arises is: what are the significant elements in the conciliation procedure of both countries and how do these elements impact the process and success rate? This research attempts to answer this question.